2000
DOI: 10.1046/j.1365-2745.2000.00479.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced growth and seed set following chemical induction of pathogen defence: does systemic acquired resistance (SAR) incur allocation costs?

Abstract: Summary1 Although most theories on plant defence assume that costs will result from the production and maintenance of defensive traits, studies on the costs of induced defence against pathogens are comparatively rare. 2 We focus on ®tness costs resulting from the chemical induction of systemic acquired resistance (SAR), a rather unspeci®c form of defence, which can be induced by and is eective against a broad spectrum of bacteria, fungi and viruses.3 We used a model system in which we treated wheat plants that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
177
0
14

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 261 publications
(204 citation statements)
references
References 52 publications
13
177
0
14
Order By: Relevance
“…A number of studies of constitutive and induced defense support the prediction that costs of defense increase under more severe nutrient and competition stress. For in-stance, under conditions of nutrient limitation, costs of resistance to a fungal pathogen and an aphid in lettuce (Bergelson 1994) and costs of systemic acquired resistance to pathogens in spring wheat (Heil et al 2000) appear to be higher than under more favorable nutrient conditions. Several studies have shown that costs can also increase under more competitive conditions (Bazzaz et al 1987;Agrawal 2000;Van Dam and Baldwin 2001).…”
mentioning
confidence: 96%
“…A number of studies of constitutive and induced defense support the prediction that costs of defense increase under more severe nutrient and competition stress. For in-stance, under conditions of nutrient limitation, costs of resistance to a fungal pathogen and an aphid in lettuce (Bergelson 1994) and costs of systemic acquired resistance to pathogens in spring wheat (Heil et al 2000) appear to be higher than under more favorable nutrient conditions. Several studies have shown that costs can also increase under more competitive conditions (Bazzaz et al 1987;Agrawal 2000;Van Dam and Baldwin 2001).…”
mentioning
confidence: 96%
“…A cost-benefit balance of salicylic acid (SA)-inducible defenses against pathogens has also been supposed. In wheat, Heil et al (6) demonstrated costs of SA-inducible defenses on growth and seed set. In Arabidopsis, Cipollini (7) showed that exogenously applied SA reduced seed production.…”
mentioning
confidence: 99%
“…Porém, em outros casos, não há incrementos na produtividade, ou até há redução da mesma, ainda com drástica redução da doença (9, 10,13,22). Portanto, a expressão da defesa pode reduzir a produtividade, a ponto de ser o custo maior do que o benefício?…”
unclassified